Metode Saintifik Dalam Pembelajaran Bahasa Jerman Dengan Tema Unterwegs - Willyam Gunawan Tampubolon; Intan Hartanti Sitompul; Monica Destauli Harianja (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2024)
This study to explore the application of scientific methods in German language learning with the theme "Unterwegs". The research was conducted in the context of a Micro Learning course involving 34 students. By implementing 11 indicators of the scientific approach and five main steps, namely observation/observation, asking questions, gathering information, association/information gathering and communication. This research shows that the scientific method can improve learning quality and student engagement. The results confirm that the scientific approach applied flexibly and creatively is not only effective but can also deepen students' understanding of the material. The findings provide important insights for the development of more effective and engaging language teaching methods.